2022
DOI: 10.3389/fonc.2022.970237
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in access to care among patients with appendiceal or colorectal cancer and peritoneal metastases: A medicare insurance-based study in the United States

Abstract: BackgroundPrior studies attempting to identify disparities in the care of patients with appendiceal (AC) or colorectal cancer (CRC) with peritoneal metastasis (PM) are limited to single-institution, highly selected patient populations. This observational cohort study sought to identify factors associated with specialty care for Medicare beneficiaries with AC/CRC-PM.Materials and methodsPatients >65 years old in the United States diagnosed with AC/CRC and isolated PM were identified within the Medicare S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Perhaps this variable alone reflects socioeconomic differences and disparities that contribute to access to care. For example, in a recent Medicare-based cohort study of individuals in the United States 65 years and older with colorectal peritoneal metastases, the authors demonstrated that living further away from an HIPEC center and higher measured social vulnerability were independently associated with lower odds of accessing CRS/HIPEC [29]. This, along with our data, advocates for increased CRS/HIPEC access and the treatment of appendiceal cancer for diverse patient populations.…”
Section: Discussionsupporting
confidence: 64%
“…Perhaps this variable alone reflects socioeconomic differences and disparities that contribute to access to care. For example, in a recent Medicare-based cohort study of individuals in the United States 65 years and older with colorectal peritoneal metastases, the authors demonstrated that living further away from an HIPEC center and higher measured social vulnerability were independently associated with lower odds of accessing CRS/HIPEC [29]. This, along with our data, advocates for increased CRS/HIPEC access and the treatment of appendiceal cancer for diverse patient populations.…”
Section: Discussionsupporting
confidence: 64%
“… 5 However, previous studies showed significant disparities in access to CRS-HIPEC based on hospital of diagnosis. 6 , 7 …”
mentioning
confidence: 99%
“…While a substantial body of literature emphasizes the reduction of inequalities in access to care, it primarily focuses on disparities driven by factors such as socioeconomic status (SES), race and ethnicity (e.g., 10 12 ). Despite numerous studies illustrating inter-hospital variation in access to care (e.g., 6 , 7 ), limited attention has been given to the effects of (national) efforts aimed at reducing such disparities. Hence, the current study assessed whether the variation in utilization of CRS-HIPEC, and, as a consequence, survival, of patients with isolated synchronous PMCRC reduced since national efforts were initiated.…”
mentioning
confidence: 99%